An individual-supported program to enhance placement in a sheltered work environment of autistic individuals mostly with intellectual disability: a prospective observational case series in an Italian community service - Maggio, Roberta; Turriziani, Laura; Campestre, Caterina; Di Cara, Marcella; Tripodi, Emanuela; Impallomeni, Caterina; Quartarone, Angelo; Passantino, Claudio; Cucinotta, Francesca (Frontiers in Psychiatry, 2023)
Introduction: autism spectrum disorder is a lifelong neurodevelopmental disorder. The profile of functioning in autistic people is very heterogeneous, and it is necessary to take in account individual characteristics to better support integration in the workplace. However, unemployment rates are higher for autistic people than other types of disabilities. We present a prospective case series to explore the feasibility and efficacy of an individual-supported program to enhance placement in a sheltered work environment delivered by an Italian community day care center.Methods: Autistic subjects, aged from 12 to 31 years, participated to an individual-supported program regarding employment in sheltered art workshops, integrated into the regular activity of a semiresidential center three times a week for one year. To explore their feasibility retention rate and time worked per session were registered; moreover, working methods efficacy and self-organization improvement were tracked by Likert-based rating system. Secondary outcome measures span functional levels, challenge behaviours and sensory problems.Results: All the individuals presented a good adaptation to the environment, with a significant increase in time worked per session. After one year, the intervention allowed an increase in tasks completed in 2 This is a provisional file, not the final typeset article an assigned complex job and an improvement in self-organization within the work schedule in a group of subjects consisting mainly of severe to moderate levels of autism severity (86.6%). Finally, we observed a significant increase in Independent Functioning areas of the TEACCH Transitional Assessment Profile. Challenge behaviors and sensory problems were also recorded.This case series supports the idea that individual-supported programs for placement in sheltered job environments delivered by a community day care centers could be feasible and effective for ASD with higher levels of severity and co-occurred intellectual disability. Further targeted studies based on community models and accessible methods need to be planned to define the effectiveness of the intervention and promote improved practice at the community level with better social impact.